Repackaging LIS professionals and libraries for the fourth industrial revolution. Issue 8 (5th June 2020) - Tella, Adeyinka
Abstract : Purpose: The purpose of this paper is to discuss the need for African Library Schools to repackage their curriculum to be able to produce graduates that will match up with jobs demand in the fourth industrial revolution (4IR) era. The discussion argued for the review of African Library Schools, identified the technologies that drive the 4IRs which LIS graduates will be working with, if employed, and relevant skills needed for functionality in the era. Design/methodology/approach: This viewpoint adopts discussion method with reference to some review of literature to argue the pints. Findings: This viewpoint finds out that to be relevant in the 4IR, LIS graduate will have to possess the required skills relevant to function in the 4IR. The skills identified among other are information curation, in-depth research, digital scanning, preservation, cloud data expansion, collaboration, teaching and facilitation, analytical thinking and innovation, active learning and learning strategies. Originality/value: This paper is an original idea from the author and has been published or submitted to any platform. This paper is original because it has been able to emphasise that African LIS schools should work closely with the employer to make sure their courses and curriculum are designed in such a way to teach employability skills. Moreover, this paper is important, as it made it clear that there is need to ensure removal of barriers to implementing better assessment and training and providing much-needed funding and resources to support the efforts. LIS graduates or those in training should also work to develop in-demand skills and learn to use tools that reveal their capabilities to their potential employers.